2011
DOI: 10.1109/tvt.2010.2091293
|View full text |Cite
|
Sign up to set email alerts
|

Fast Estimation of Relations Between Aggregated Train Power System Data and Traffic Performance

Abstract: Abstract-Transports on rail are increasing and major railway infrastructure investments are expected. An important part of this infrastructure is the railway power supply system. The future railway power demands are not known. The more distant the uncertain future, the greater the number of scenarios that have to be considered. Large numbers of scenarios make time demanding (some minutes, each) full simulations of electric railway power systems less attractive and simplifications more so.The aim, and main cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Comparing both schemes, it can be observed that edge (6, 7) is invariant. Edges (1, 5), (3,5) and (2, 7) also appear in both instants. Figure 14 shows the graphs corresponding to the two instants.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Comparing both schemes, it can be observed that edge (6, 7) is invariant. Edges (1, 5), (3,5) and (2, 7) also appear in both instants. Figure 14 shows the graphs corresponding to the two instants.…”
Section: Resultsmentioning
confidence: 98%
“…It can be observed that the edge representing the adjacency (6,7), is e 19 in both cases. Furthermore, the adjacencies appearing in both cases ((1, 5), (3,5) and (2, 7)) are represented by the same edges (e 4 , e 13 and e 11 ). Table 4 shows the "active" and "non active" edges at each instant and Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The matrix equation (3) represents the KCL in all nodes. It has n N equations and (n N + n B ) unknowns, being n N the number of nodes and n B the number of branches.…”
Section: Algorithm Description a Core Bfs Algorithmmentioning
confidence: 99%
“…The authors run a steady state simulations at each simulation instant neglecting the transients between successive instants as it was proposed in [8]. This approach, known as stationary equivalent method for moving loads, is widely accepted among the authors, not only for modelling DC traction networks, but also for modelling AC traction networks for high speed trains [2][3][4][5][9][10][11][12][13][14]. This method assumes that the speed of the trains is not very high to induce pronounced electrical transients and the dc traction network slowly moves from one state to another as the locations and the input power of the trains vary.…”
mentioning
confidence: 99%